Hot node limitations and impact of taxonomic resolution on phylogenetic divergence patterns: A case study on Ecuadorian ethnomedicinal flora - Darío Atienza‐Barthelemy; Manuel J. Macía; Rafael Molina‐Venegas (Plants, People, Planet)
Summary Societal Impact Statement Novel phylogenetic approaches have emerged in recent years to study traditional medicinal plants, aiming to identify potential sources of new drugs. This line of research holds considerable promise yet remains in its early stages. Here, we examine the prevalent methods employed in the field, revealing the impact of methodological choices that have often been made arbitrarily. We also highlight a widespread misconception regarding ‘hot node analysis’, a tool gaining popularity for identifying plants with high bioactive potential. Our findings should advance future research aimed at guiding the selection of promising candidates for bioprospection. Summary Advances in phylogenetics offer a ground‐breaking approach to analysing ethnobotanical data. This line of research typically involves calculating the degree of phylogenetic clustering (i.e. phylogenetic divergence) of a set of medicinal plants and identifying clades with a significant overabundance of these plants, known as hot nodes, which are purportedly responsible for the clustering patterns. However, despite showing great promise, the adequacy of this procedure remains to be tested, and the results have so far been inconclusive and, at times, contradictory. Here, we examine two key elements through a case study of Ecuadorian medicinal flora: the impact of taxonomic resolution (species‐ and genus‐level data) on phylogenetic divergence metrics (Mean Pairwise Distance; MPD, and Mean Nearest Taxon Distance; MNTD), and the efficacy of the hot node analysis in identifying clades that significantly influence these metrics. To identify clades with a significant impact on MPD and MNTD, we implemented a jackknifing procedure and compared outcomes with the hot nodes. Phylogenetic divergence was strongly dependent on the taxonomic resolution, with clustering mainly revealed by MPD at the genus level. Further, the hot nodes incompletely matched those with significant influence on MPD and MNTD according to the jackknifing analysis. We highlight the impact of taxonomic resolution on commonly used phylogenetic divergence metrics and the limitations of hot nodes in identifying influential clades, stressing the potential of alternative jackknifing techniques. We recommend the use of the most resolved tree possible and combining jackknifing with hot node analyses as complementary sources to pinpoint clades for bioprospection.